2001
DOI: 10.1101/gr.190901
|View full text |Cite
|
Sign up to set email alerts
|

BADGE, BeadsArray for the Detection of Gene Expression, a High-Throughput Diagnostic Bioassay

Abstract: Several methods are presently available for gene expression analysis. However, few of them are suitable for detection of moderate numbers of genes in thousands of samples with high speed and low cost. There is great demand for such a method for use in diagnostics and screening. To address this need, we have developed an assay for gene expression analysis using microspheres and a fluidic instrument made by Luminex. The assay is named Beads Array for the Detection of Gene Expression (BADGE). BADGE can monitor up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 28 publications
1
58
0
Order By: Relevance
“…Other high-throughput detection methods, such as bead-based detection or 'arrays of arrays' are, in principle, feasible 9,10 .…”
Section: E T T E R Smentioning
confidence: 99%
“…Other high-throughput detection methods, such as bead-based detection or 'arrays of arrays' are, in principle, feasible 9,10 .…”
Section: E T T E R Smentioning
confidence: 99%
“…Oligonucleotide capture probes were coupled to their respective microspheres (Table 1) following the protocol set forth by Yang et al (2001). Luminex xMAP™ bead stocks were sonicated using a Branson Ultrasonic Cleaner (Branson) at 40 kHz for 1 min to ensure an even distribution of beads in solution prior to being aliquoted.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA harvested from each subset was analyzed in parallel by the mirMASA assay, a liquidphase multiplex analytical approach utilizing hybridization probes for 114 miRNAs. 17,21,23 Pre-validation studies using synthetic miRNAs showed that s.d.s for replica determinations were 2-9% of the mean value. Readouts were normalized to the hybridization reaction of 5S RNA, the expression of which in tumor and normal tissues of individual patients did not differ significantly from one another (P ¼ 0.38; Student's two-sided paired t-test) in our study population.…”
Section: Human Prostate Cancer Signature By Array Analysismentioning
confidence: 99%
“…miRNA binding was quantified with Fluorokine MultiAnalyte Profiling (xMAP) flow cytometry of the Luminex platform. 21 Each set of color-coded microsphere (bead) is covalently coupled with a capture oligonucleotide and a biotin-labeled detection oligonucleotide. The 12-nt capture oligonucleotide recognizes the 3 0 end portion of the miRNA, whereas a short (8-10 nt), biotin-labeled detection oligonucleotide hybridizes to the 5 0 end of the same miRNA.…”
Section: Rna Extractionmentioning
confidence: 99%